Analysis, Design, and Actual Fabrication of a Hybrid Microstrip-SIW Bandpass Filter Based on Cascaded Hardware Integration at X-Band - Guvenli, Kemal; Yenikaya, Sibel; Secmen, Mustafa (Elektronika ir Elektrotechnika, 2021)
In this paper, the Microstrip-Substrate Integrated Waveguide (M-SIW) bandpass filter is designed, simulated, and fabricated based on the theoretical analysis. The Substrate Integrated Waveguide (SIW) highpass filter and the microstrip lowpass filter are combined in a hybrid design to achieve the M-SIW bandpass filter in the X-band. This design is more comprehensible and easier to achieve a bandpass filter at a desired frequency. The SIW highpass filter and the microstrip lowpass filter are connected in series to achieve the bandpass filter. To the measured results of the fabricated M-SIW bandpass filter, the center frequency is 10.20 GHz and the bandwidth is 2.40 GHz. When the analytical and measurement results are compared, the frequency change in the cut-off frequency is 6.02 % and the frequency change in the bandwidth is 8.74 %. It is generally seen that analytical, simulation, and measurement results are compatible with each other. The M-SIW bandpass filter can be broadly used in radar, Worldwide Interoperability for Microwave Access (WiMAX), and satellite technologies. The filters are simulated in Computer Simulation Technology (CST) Studio Suite.